Apparent diffusion coefficient (ADC) values of serous, endometrioid, and clear cell carcinoma of the ovary: pathological correlation. (July 2020) - Ono, Takafumi; Kishimoto, Keiko; Tajima, Shinya; Maeda, Ichiro; Takagi, Masayuki; Suzuki, Nao; Mimura, Hidefumi
Background: Primary epithelial ovarian cancer is divided into several subtypes. The relationships between apparent diffusion coefficient (ADC) values and their subtypes have not yet been established. Purpose: To investigate whether ADC values of epithelial ovarian cancer vary according to histologic tumor cellularity and evaluate the difference of clear cell carcinoma (CCC), high-grade serous carcinoma (HGSC), and endometrioid carcinoma (EC). Material and Methods: This retrospective study included 51 cases of epithelial ovarian cancer (17 CCC, 20 HGSC, and 14 EC) identified by magnetic resonance imaging with pathological confirmation. All patients underwent diffusion-weighted imaging and the ADC values of lesions were measured. We counted the tumor cells in three high-power fields and calculated the average for each case. The Spearman's correlation coefficient test was used to analyze correlation between ADC values and tumor cellularity. The ADC values of HGSC, EC, and CCC were compared using the Steel–Dwass test. Results: The ADC values of all cases were significantly inversely correlated with tumor cellularity ( rs  = −0.761; P  < 0.001). The mean ± SD ADC values (×10 −3 mm 2 /s) of CCC, HGSC, and EC were 1.24 ± 0.17 (range 0.98--1.65), 0.84 ± 0.10 (range 0.67--1.06), and 0.84 ± 0.10 (range 0.67--1.07). The mean ± SD tumor cellularity of CCC, HGSC, and EC was 162.88 ± 63.28 (range 90.33--305.67), 440.60 ± 119.86 (range 204.67--655.67), and 461.02 ± 81.86 (range 333.33--602.33). Conclusion: There is a significant inverse correlation between ADC values and tumor cellularity in epithelial ovarian cancer. The mean ADC value of CCC was higher than those of HGSC and EC, seemingly due to the low cellularity of CCC.